Variable Severity of B-Thalassemia/Hemoglobin E Disease - the Genetic Factors - Sunarto Sunarto (Paediatrica Indonesiana, 1997)
Hemoglobin E (Hb E) is prevalent in Southeast Asia. Heterozygotes give no manifestation, even homozygotes show no manifestation or only slight anemia. However, compound heterozygote with 6-thalassemia gives anemia with variable severity. The severely affected individuals show anemia similar to homozygous 6-thalassemia. Many factors play a role in determining the severity. SThnl/6E patients have increased superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities. The increased GSH-Px is thought to be needed for the elimination of hydrogen peroxide produced by SOD decomposition of peroxide. The content of antioxidants vitamine E and C is reduced, whereas MDA, the final product of lipid peroxidation increases significantly. The genotype of the Xmn 1 polymorphism, -158 bases upstream from the transcription site of the n-globin and the level of Hb F are associated with clinical severity, but the extent of the S' -globin mRNA cryptic splicing is more associated with the severity of tire manifestation than does the pattern of the Xmn I polymorphism.